(untitled) (Research, Society and Development, 2021)
One of the main difficulties and challenges for the consolidation and operationalization of the environmental health policy in the Brazil’s Unified Public Health System (SUS) is the establishment of both processes and pedagogical strategies for training and professional education at high school and undergraduate levels that are capable to answer the demands and needs of this area. This study aimed to discuss the importance of the formative processes of the Professional Qualification Course in Environmental Health Surveillance and its relevance as a qualification strategy for the SUS. The methodology consisted in the qualitative analysis on the teaching-learning dimensions involved in the establishment of this formative strategy. The observed results indicate to the force of technical qualification in the development of skills and competencies with a purpose to criticality in working with the SUS. It was concluded that this course brought significant learning to the strategy of training workers attentive to the determinants and conditioning factors in health.